1996
DOI: 10.1074/jbc.271.47.29698
|View full text |Cite
|
Sign up to set email alerts
|

A Significant Fraction of Functional SecA Is Permanently Embedded in the Membrane

Abstract: SecA has been suggested to cycle on and off the cytoplasmic membrane of Escherichia coli during protein translocation. We have reconstituted 35 S-SecA onto SecA-depleted membrane vesicles and followed the fate of the membrane-associated 35 S-SecA during protein translocation. Some 35 S-SecA was released from the membranes in a translocation-independent manner. However, a significant fraction of 35 S-SecA remained on the membranes even after incubation with excess SecA. This fraction of 35 S-SecA was shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 64 publications
(182 reference statements)
5
64
1
Order By: Relevance
“…Centrifugation though sucrose to remove low affinity bound SecA molecules decreased the SecA associated with native IMVs to 6.5 g/mg of IMV protein, while no further decrease in the SecA content of urea-treated IMVs was observed after sedimentation through sucrose. These values are in good agreement with earlier estimates of the amount of "integral" SecA in IMVs (22). It should be noted that the membranes are centrifuged over sucrose gradients during IMV preparation (6), serving to further reduce the contribution of nonspecifically bound SecA molecules.…”
Section: An Intact Membrane Is Required For Full Protease Resistance supporting
confidence: 80%
See 1 more Smart Citation
“…Centrifugation though sucrose to remove low affinity bound SecA molecules decreased the SecA associated with native IMVs to 6.5 g/mg of IMV protein, while no further decrease in the SecA content of urea-treated IMVs was observed after sedimentation through sucrose. These values are in good agreement with earlier estimates of the amount of "integral" SecA in IMVs (22). It should be noted that the membranes are centrifuged over sucrose gradients during IMV preparation (6), serving to further reduce the contribution of nonspecifically bound SecA molecules.…”
Section: An Intact Membrane Is Required For Full Protease Resistance supporting
confidence: 80%
“…Since SecA has preexisting domains of 65 and 30 kDa (8,12,19) and the resistance of these domains to proteolytic attack is altered by physiological ligands such as preprotein, ATP, and SecYEG (12,20,21), it has been questioned whether the conformational change of SecA during translocation includes actual insertion across the membrane toward the periplasm (21). Recently, it has even been proposed that lipid-associated SecA catalyzes preprotein translocation (22,23). Finally, the conformations, associations, and specific translocation activity of the endogenous SecA that copurifies with inner membrane vesicles have not been defined.…”
mentioning
confidence: 99%
“…Because the 30-kDa fragment could be chased by an excess of non-radioactive SecA, SecA was proposed to alternate between a cytosolic and membrane-associated state during its reaction cycle (21). However, other studies failed to demonstrate a translocation-dependent dissociation of membranebound SecA and concluded that membrane cycling is not an essential feature for protein translocation (22). The SPR results presented here demonstrate directly that SecA can dissociate from the activated SecYEG complex during a translocation cycle.…”
Section: Discussionmentioning
confidence: 64%
“…Although several studies have addressed the order of events during protein translocation, relatively little is known about the SecASecYEG interaction in this process. SecA has been proposed to partition between the cytoplasm and the inner membrane during its reaction cycle (19,21), but other studies question the SecA membrane cycling model as a significant fraction of active SecA remains stably associated with the membrane throughout the translocation reaction (22). Indirect evidence, using SecA bound to a liposome surface instead to SecYEG, suggests that ATP hydrolysis drives the release of the SecA-bound preprotein (19).…”
mentioning
confidence: 99%
“…One current model proposes that SecA undergoes ATPdriven cycles of insertion and retraction at SecYE, thereby promoting the stepwise translocation of proteins (15)(16)(17). Another model posits that protein translocation takes place from SecA that is permanently inserted into the plasma membrane (18).…”
mentioning
confidence: 99%